2018
DOI: 10.12688/f1000research.11395.4
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 novel variation V1736D and in silico analysis of SNP Q356R in Sudanese patients with breast cancer

Abstract: Open Peer Review AbstractBreast cancer (BC) remains one of the leading causes of death Background: in women worldwide. The deleterious mutation has a significant role in BRCA1 developing BC, and the risk has been estimated to be 46-87%. Many studies emphasize the need for mining gene mutations that might have a role BRCA1 in BC pathogenesis and could affect early disease onset. This study was conducted to screen for possible pathogenic single nucleotide polymorphisms (SNPs) in , targeting three regions: two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Previously, similar studies showed the association of rs1799950 (BRCA1) with Breast cancer risk. The homozygous mutant genotype was found to be associated with breast cancer risk in the Saudi population [39] while the heterozygous genotype was found to be associated with breast cancer risk in Sudanese [40]. rs1799950 genotype exhibited a positive relationship with family history, nulliparity, menstrual status, ER-and PR-status, but displayed negative correlation with HER2 abundance.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, similar studies showed the association of rs1799950 (BRCA1) with Breast cancer risk. The homozygous mutant genotype was found to be associated with breast cancer risk in the Saudi population [39] while the heterozygous genotype was found to be associated with breast cancer risk in Sudanese [40]. rs1799950 genotype exhibited a positive relationship with family history, nulliparity, menstrual status, ER-and PR-status, but displayed negative correlation with HER2 abundance.…”
Section: Discussionmentioning
confidence: 93%